When dinos dawned, mammals got munched, and Pterosaurs took flight : a cartoon pre-history of life in the Triassic - Bonner, Hannah (National Geographic Children's Books, 2012)
"In the style of WHEN BUGS WERE BIG and WHEN FISH GOT FEET this book discusses all the exciting developments of the Triassic Age, from the split of Pangaea into Gondwanaland and Laurasia, to the first appearance of the dinosaurs. There were pterosaurs (flying reptiles), the first flowering plants, humongous sea creatures, early turtles, and the first coral reefs. Early mammals also appeared in the Triassic, and there were several dramatic extinction events."--